(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Translating science fiction presents unique lexical challenges due to its reliance on invented terminology, culturally specific references, and imaginative constructs that defy conventional linguistic frameworks. This study examines the lexical difficulties encountered in translating Ray Bradbury’s Fahrenheit 451, a seminal science fiction novel, into various languages. Focusing on key terms such as “fireman,” “salamander,” and “Mechanical Hound,” the analysis explores how translators navigate semantic ambiguity, cultural adaptation, and neologism retention. Findings reveal those successful translations balance fidelity to the source text with accessibility for target audiences, often requiring creative strategies like explanatory footnotes or lexical substitution. The study underscores the broader implications of these challenges for translating speculative fiction, emphasizing the need for translators to act as cultural mediators in preserving the genre’s innovative essence.